Effect of polarization voltage on the surface componentization and biocompatibility of micro-arc oxidation modified selective laser melted Ti6Al4V. (15th May 2019) - Chen, Ziyu; Yan, Xingchen; Chang, Yu; Xie, Shiming; Ma, Wenyou; Zhao, Guorui; Liao, Hanlin; Fang, Hang; Liu, Min; Cai, Daozhang
Abstract: The technique of selective laser melting (SLM) has been widely applied as an additive manufacturing method in fabricating Ti6Al4V parts. However, the inert surface of the SLM titanium alloy restricts its biomedical application especially as the bone implants material. In this work, micro-arc oxidation (MAO) was proposed to improve the biological performance by forming a ceramic coating containing calcium (Ca) and phosphorus (P) on the SLM Ti6Al4V surface. The influence of polarization voltage, which ranged from 200 to 400 V, on the characteristics of the modified samples and their biomedical properties have been evaluated. The microstructure, morphology, and chemical compositions of MAO coatings prepared by different voltages were characterized through scanning electron microscopy (SEM) and x-ray diffraction (XRD). Biocompatibility studies, including cytotoxicity analysis and cell proliferation study, were performed using rat bone marrow stem cells (rBMSCs). The results showed that hydroxyapatite coatings were formed on the surface of SLM Ti6Al4V and well combined with the matrix after MAO treatment. Excessive voltage and too low voltage are not conducive to the formation of crack-free porous coating. Moreover, the coatings showed nontoxicity effect and better cell proliferation ability than the as-built sample. Thus, it can be expected that proper MAO treatment can improve bioactivity of the SLM Ti6Al4V implant.